Zirconium oxide composite sintered body and method for producing same
By adding ZrO2, HfO2 and Nb2O5/Ta2O5 to the zirconia sintered body and using capping elements or ions, the grain boundary strength is reduced, and the problem of difficult machining of zirconia sintered body is solved in the dentistry, realizing dental treatment time The shortening and reduction of tool consumption improve the processing efficiency and economicality of dental patches.
Patent Information
- Application Number
- CN202380044109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-10
AI Technical Summary
In dental applications, zirconia sintered bodies are difficult to perform mechanical processing in sintered state due to their high hardness, resulting in a prolonged dental treatment time, fast consumption of processing tools, low productivity and economicality.
The zirconia composite sintered body formed by using ZrO2 and HfO2 as phase change stabilizers, Nb2O5 and/or Ta2O5, and adding capping elements or ions, thereby reducing the grain boundary strength at the crystal boundary and improving mechanical processing properties.
It realizes efficient mechanical processing in the sintered body state, shortens dental treatment time, reduces tool consumption, improves productivity and economy, while maintaining the intensity and light transmittance of dental patches.
Smart Images

Figure BDA0005161818180000361 
Figure BDA0005161818180000371 
Figure BDA0005161818180000381
Abstract
Description
Technical Field
[0001] The present invention relates to a zirconia composite sintered body and a method for producing the same. More specifically, the present invention relates to a zirconia composite sintered body having excellent strength and light transmittance and excellent processability in a sintered body state and a method for producing the same. Background Art
[0002] Ceramics made of metal oxides are widely used in industry. Among them, sintered zirconium oxide is used for dental materials such as dental prostheses due to its high strength and aesthetic properties.
[0003] Since zirconia sintered bodies are excellent in strength, they are unlikely to break when used for dental materials such as prostheses. In addition, since zirconia sintered bodies are highly translucent, they are difficult to stain in the oral cavity, so they are also excellent in aesthetics. On the other hand, after being made into a sintered body in a completely sintered state, they are almost impossible to process using a dental processing machine because of their high hardness. For example, if a zirconia sintered body having a cubic shape is machined in order to obtain a zirconia sintered body having a shape consistent with the shape of the patient's teeth, the consumption of metal processing tools becomes very large, and a lot of time is required to manufacture only one dental prosthesis.
[0004] Based on such circumstances, when a zirconia sintered body is used as a dental material, it is usually not a completely sintered sintered body, but a pre-sintered body in a semi-sintered state that is easy to process is processed into the shape of a desired dental prosthesis, and then further sintered to produce a sintered body processed into the shape of a target dental prosthesis. Thereafter, the sintered body is subjected to a slight adjustment process so that the sintered body having the shape of a dental prosthesis is suitable and does not feel incompatible when it is installed in the oral cavity of a patient in a dental hospital.
[0005] In recent years, when processing a calcined body into a desired shape of a dental prosthesis, machining based on a CAD / CAM system is used to obtain a shape that matches the tooth of the patient's treatment site, and calcined bodies (polished blanks) for CAD / CAM systems are often used.
[0006] As described above, when zirconia sintered bodies are used for dental material applications, due to the unique problems in sintering zirconia, large-scale machining is avoided after the sintered bodies are made, and the processing of the sintered bodies is limited to the level of fine adjustment when they are installed in the patient's mouth in a dental clinic. In other words, the use of dental materials is handled based on the staged physical property changes caused by the sintering of zirconia.
[0007] Furthermore, in dental treatment, in consideration of the unique conditions caused by the physical properties of the above-mentioned zirconia sintered body, treatment is generally performed through the following multiple steps: a step of obtaining information on the shape of the patient's oral cavity, such as dentition information; a step of machining a calcined body (grinded blank) into the shape of a desired dental prosthesis by a CAD / CAM system based on the acquired information; a step of sintering the calcined body having the shape of the desired dental prosthesis to obtain a sintered body; and a step of performing minute adjustment processing on the sintered body in a manner that is appropriate and does not feel incompatible when installed in the patient's oral cavity in a dental hospital.
[0008] Thus, in dental treatment using a dental prosthesis made of sintered zirconium oxide, it is difficult to complete all the above steps in one visit to the hospital. Therefore, in many cases, even if it is just one tooth, multiple visits to the dental hospital are required, and the treatment period from the start to the end of the treatment often takes more than one month.
[0009] On the other hand, patients want to reduce the number of visits to the hospital and complete treatment in a short period of time in order to shorten the time until new artificial teeth are installed after treatment and reduce the burden of going to the hospital.
[0010] Assuming that the zirconia sintered body can be extensively machined, there is no need to temporarily machine the pre-burned body and then manufacture the sintered body by sintering. After obtaining information on the shape of the patient's oral cavity, the unprocessed sintered body is machined into the shape of the desired dental prosthesis through a CAD / CAM system based on the information, installed in the patient's oral cavity and fine-tuned, completing the dental treatment in one day.
[0011] In addition, when using dental prostheses, it is possible to complete dental treatment in one day when using materials other than zirconia, such as lithium disilicate glass ceramics and feldspar glass ceramics. However, in the case of zirconia sintered bodies, there are unique circumstances caused by the physical properties of zirconia sintered bodies, making it difficult to achieve.
[0012] As described above, since the demand for zirconium oxide is high from the perspectives of strength and aesthetics, along with the increasing demand for shortening the treatment period, a zirconium oxide sintered body has been proposed which has excellent machinability in the sintered body state and can be processed from a prismatic or disc-shaped ground blank into the shape of a desired dental prosthesis (for example, Patent Documents 1 and 2).
[0013] For example, Patent Document 1 discloses a machinable zirconia and a method for manufacturing the same, wherein the machinable zirconia is a sintered body formed in a manner comprising a tetragonal zirconia composite powder and a TiO2 nanopowder having a mass ratio greater than 0 mass % and less than 2.5 mass % relative to the aforementioned zirconia composite powder, wherein the tetragonal zirconia composite powder contains 79.8 to 92 mol % of ZrO2 and 4.5 to 10.2 mol % of Y2O3, and 3.5 to 7.5 mol % of Nb2O5 or 5.5 to 10.0 mol % of Ta2O5.
[0014] In addition, Patent Document 2 discloses a machinable zirconium oxide composition and a method for manufacturing the same using a raw material, wherein the raw material contains 78 to 95 mol % of ZrO2, 2.5 to 10 mol % of Y2O3, and 2 to 8 mol % of Nb2O5 and / or 3 to 10 mol % of Ta2O5, and the main crystalline phase of ZrO2 is monoclinic.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 2015-127294
[0018] Patent Document 2: International Publication No. 2021 / 132644 Summary of the invention
[0019] Problems to be solved by the invention
[0020] The zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined even in a sintered state. However, the processing time for cutting out dental prostheses is prolonged, and there is room for improvement from the viewpoint of shortening treatment time.
[0021] In addition, although the zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined, the number of dental prostheses obtained by continuous processing using one processing tool is small and the processing tool is consumed quickly. Therefore, there is a problem that the frequency of replacing the processing tool increases, the tool replacement time increases, and the productivity and economic efficiency decrease.
[0022] Furthermore, if the hardness of the material is reduced in order to improve machinability, there is a problem that the strength of the material is reduced.
[0023] An object of the present invention is to provide a zirconia composite sintered body having strength and light transmittance suitable for dental use and excellent machinability.
[0024] Solutions to Solve Problems
[0025] In order to solve the above-mentioned problems, the present inventors conducted in-depth research and found that the problems can be solved by including capping elements or ions in a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5 in a specified proportion. Based on this insight, further research was carried out to complete the present invention.
[0026] That is, the present invention includes the following inventions.
[0027] [1] A zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconia, and Nb2O5 and / or Ta2O5,
[0028] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0029] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0030] The content of the stabilizer is 1 to 12 mol%.
[0031] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0032] The zirconia composite sintered body further includes elements or ions derived from a capping agent.
[0033] [2] The zirconium oxide composite sintered body according to [1], wherein the content of the element or ion derived from the capping agent is greater than 0 mol% and less than 5.0 mol% relative to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5.
[0034] [3] A zirconia composite sintered body according to [1] or [2], wherein the element or ion derived from the capping agent is an element or ion belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy smaller than that of the elements of Group 18 of the same period, and / or an element or ion having a high electron affinity.
[0035] [4] The zirconium oxide composite sintered body according to [3], wherein the element or ion derived from the capping agent includes at least one element or ion selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
[0036] [5] The zirconium oxide composite sintered body according to any one of [1] to [4], wherein when the content of the aforementioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0037] [6] The zirconium oxide composite sintered body according to any one of [1] to [5], wherein the stabilizer contains Y2O3 and / or CeO2.
[0038] [7] A zirconium oxide composite sintered body according to any one of [1] to [6], further comprising a zirconium oxide strengthener, wherein the content of the zirconium oxide strengthener is greater than 0 mass % and less than 5.0 mass % relative to the total of 100 mass % of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5.
[0039] [8] The zirconia composite sintered body according to [7], wherein the zirconia reinforcing agent contains TiO2 and / or Al2O3.
[0040] [9] The zirconia composite sintered body according to [7], wherein the zirconia reinforcing agent contains TiO 2 , and the content of TiO 2 is 0.6 to 3.7% by mass.
[0041]
[10] The zirconia composite sintered body according to any one of [1] to [9], wherein the average grain size of the zirconia composite sintered body is 0.5 to 5.0 μm.
[0042]
[11] The method for producing a zirconia composite sintered body according to [1] comprises:
[0043] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,
[0044] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0045] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0046] The content of the stabilizer is 1 to 12 mol%.
[0047] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0048] The raw material composition further comprises a capping agent; and
[0049] A step of sintering the molded body.
[0050]
[12] The method for producing a zirconia composite sintered body according to
[11] , wherein the terminal capping agent contained in the raw material composition is a compound that can form a monovalent ion,
[0051] The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.
[0052]
[13] The method for producing a zirconium oxide composite sintered body according to
[11] or
[12] , wherein in the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO2 and HfO2.
[0053]
[14] The method for producing a zirconia composite sintered body according to any one of
[11] to
[13] , wherein the step of sintering the molded body comprises:
[0054] The sintering process is performed at 1300-1680°C, and
[0055] A process of performing HIP treatment at 1200°C or above.
[0056]
[15] The method for producing a zirconia composite sintered body according to
[14] , comprising, after the HIP treatment step, a step of performing a heat treatment at 1400° C. or less in air or in an oxygen-excess atmosphere.
[0057] Effects of the Invention
[0058] According to the present invention, it is possible to provide a zirconia composite sintered body which has strength and light transmittance suitable for dental use and is excellent in machinability.
[0059] In addition, according to the present invention, a zirconia composite sintered body can be provided, which can be machined in the state of a sintered body, and the machining time is short based on the machining, and the consumption of machining tools can be suppressed. By continuous processing using one machining tool (hereinafter also referred to as "continuous processing"), a large number of dental restorations can be cut out, and the productivity and economy are excellent.
[0060] Brief description of the attached figure
[0061] Figure 1 It is a schematic diagram showing the estimated structure of the zirconium oxide composite sintered body according to the present invention.
[0062] Figure 2 Schematic diagram showing the presumed mechanism of action of the element or ion derived from the capping agent related to the present invention. DETAILED DESCRIPTION
[0063] The zirconia composite sintered body of the present invention comprises ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia (hereinafter also referred to as "stabilizer"), and Nb2O5 and / or Ta2O5.
[0064] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0065] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0066] The content of the stabilizer is 1 to 12 mol%.
[0067] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0068] The zirconia composite sintered body further includes elements or ions derived from a capping agent.
[0069] The zirconia composite sintered body of the present invention refers to a state (sintered state) in which ZrO2 particles (powder) are completely sintered. It should be noted that in this specification, the upper limit and lower limit of the numerical range (the content of each component, the ratio calculated from each component, the value and each physical property, etc.) can be appropriately combined. In this specification, machining includes cutting and grinding. In addition, machining can be any of wet machining and dry machining, without special limitation.
[0070] In the present specification, elements or ions derived from capping agents (hereinafter also referred to as "capping elements or ions") refer to elements or ions that cap the ends of the bonding sites (bonding hands) of the zirconium oxide-based composite oxides in the zirconium oxide-based composite sintered body composed of zirconium oxide-based composite oxides, thereby weakening the strength of the crystal interface (hereinafter also referred to as "grain boundary") (hereinafter also referred to as "grain boundary strength").
[0071] The capping agent can cap a portion of the crystal grain boundaries.
[0072] The term "capping" means that the target element or ion (capping element or ion) is bonded to the bonding site of the zirconium oxide-based composite oxide instead of the metal element and exists at the crystal grain boundary.
[0073] It is presumed that the capping elements or ions exist at the grain boundaries in the form of +1-valent cations or -1-valent anions, and the capped cations or anions are electrostatically repelled from each other, thereby weakening the grain boundary strength.
[0074] In the present specification, the content of each component in the zirconia composite sintered body can be calculated from the amount of raw materials charged.
[0075] In addition, the content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 in the zirconia composite sintered body can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, etc.
[0076] The content rate (mol %) of the element or ion derived from the capping agent is the external addition rate relative to the total of 100 mol % of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the element or ion derived from the capping agent in the zirconia composite sintered body can be calculated by converting the added amount (mass) of the raw materials at the time of addition into mol %.
[0077] In addition, the content rate (mass %) of the zirconia reinforcing agent is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the zirconia reinforcing agent in the zirconia composite sintered body can be calculated from the added amount (mass) of the raw materials when added.
[0078] The reason why the zirconia composite sintered body of the present invention has strength and light transmittance suitable for dental use and has high machinability and can be machined in a sintered state is not yet clear, but is presumed as follows.
[0079] It can be speculated that in the zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, due to the presence of capping elements or ions at the crystal grain boundaries, the capping elements or ions reduce the grain boundary strength in the form of +1-valent cations or -1-valent anions, act in the direction of facilitating the peeling of particles, become easier to cut, and improve machinability.
[0080] It can be inferred that the zirconium oxide composite sintered body of the present invention has the following structure, which includes: zirconium oxide particles 1 containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5, a stripping component 2 containing a capping element or ion, and further, as needed, an adhesive component 3 containing ZrO2, HfO2, Nb2O5 and / or Ta2O5, and a metal element (such as Ti, etc.) derived from the zirconium oxide strengthener.
[0081] Part of each of ZrO 2 , HfO 2 , and Nb 2 O 5 and / or Ta 2 O 5 exists in both the zirconium oxide particles 1 and the adhesive component 3 .
[0082] Furthermore, it can be inferred that in the zirconia composite sintered body of the present invention, there are grain boundaries 4 where no exfoliation component 2 exists, and exfoliation components 2 containing capping elements or ions exist appropriately at the grain boundaries, so that the grain boundary strength can be appropriately reduced while keeping the strength reduction to a minimum.
[0083] Figure 1A schematic diagram showing an estimated structure of a zirconia composite sintered body according to an embodiment including a zirconia reinforcing agent. Even in the presence of an adhesive component 3 in a zirconia composite sintered body including a zirconia reinforcing agent, the effect of reducing the grain boundary strength obtained by the exfoliation component 2 is not suppressed, and the strength can be improved.
[0084] The capping element or ion forms a +1-valent cation or -1-valent anion at the grain boundary of the zirconia composite sintered body, and combines with the bonding site of the zirconia composite oxide. Through this bonding, the cations or anions are electrostatically repelled, and the particles constituting the zirconia composite sintered body can maintain the properties of strength and light transmittance, and weaken the grain boundary strength, which plays a role in improving the machinability.
[0085] For example, Figure 2 As shown in (a), it is considered that the +1-valent cation is combined with another bonding site of the oxygen atom bonded to the metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide to replace the aforementioned metal element. Figure 2 In (a), M + Represents a +1 valent cation.
[0086] In addition, if Figure 2 As shown in (b), it is believed that the -1-valent anion is bound to the OH group on the metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide. 2+ Combined form.
[0087] Furthermore, if Figure 2 As shown in (c), it is considered that a -1 valent anion is combined with a cation derived from a metal element (such as Zr, Hf, Y, Nb or Ta) contained in the zirconium oxide composite oxide and combined with other metal elements. Figure 2 In (b) and (c), X - It represents a -1 valent anion.
[0088] exist Figure 2 In (a) to (c), the interaction between the charged points at the grain boundaries and the adsorption sites is schematically represented.
[0089] In addition, since Nb2O5 and / or Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness in the zirconia composite sintered body, the end-capping element or ion is integrated with Nb2O5 and / or Ta2O5 and acts in the direction of improving the machinability. Therefore, it is estimated that the end-capping element or ion acts as an integral part of Nb2O5 and / or Ta2O5, has the strength required for artificial teeth, and can provide excellent machinability, so in addition to shortening the machining time based on mechanical machining, it is also possible to suppress the consumption of machining tools, increase the number of dental prostheses obtained by continuous machining using one machining tool, and solve the unique problems in the continuous machining of sintered bodies.
[0090] In the zirconia composite sintered body of the present invention, the terminal elements or ions function as a free-machining agent as described above, and further, the strength and light transmittance are not seriously impaired.
[0091] The content of the capping element or ion contained in the zirconia composite sintered body of the present invention is preferably greater than 0 mol% and less than 5 mol%. From the viewpoint of better machinability and the ability to further increase the number of dental prostheses that can be continuously processed with one processing tool, it is more preferably from 0.05 mol% to 3 mol%, further preferably from 0.06 mol% to 2.5 mol%, particularly preferably from 0.07 mol% to 1.0 mol%, and most preferably from 0.08 mol% to 0.34 mol%.
[0092] In addition, when the capping element or ion contained in the zirconia composite sintered body of the present invention is a Group 17 element or ion, it is more preferably 0.2 mol% to 5 mol%, more preferably 0.3 mol% to 4 mol%, particularly preferably 0.4 mol% to 3.5 mol%, and most preferably 0.5 mol% to 3.0 mol%, from the viewpoint of better machinability and further increasing the number of dental prostheses that can be continuously processed with one processing tool.
[0093] As described above, it is important for the capping element or ion to exist at the grain boundary as a +monovalent cation or a -monovalent anion from the viewpoint of exhibiting appropriate interaction between the charged point at the grain boundary and the adsorption site.
[0094] As the capping element or ion, preferably, an element or its ion belonging to the 2nd to 7th period of the periodic table and having a first ionization energy smaller than that of the 18th group element in the same period, an element or its ion with high electron affinity, a nitrate ion, a hypochlorite ion, a chlorate ion, a perchlorate ion, a bromate ion, a permanganate ion, a metaborate ion, and a cyanide ion.
[0095] As some suitable embodiments, there can be cited zirconium oxide composite sintered bodies, wherein the aforementioned elements or their ions derived from the capping agent are elements or their ions belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy smaller than that of the 18th group elements of the same period, and / or elements or their ions with high electron affinity.
[0096] As the aforementioned elements belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy smaller than that of the 18th group elements in the same period, Cu, Ag, Li, Na, K, Rb, Cs, Fr, etc. are suitable because they are easier to obtain +1 valent cations and have better machinability.
[0097] As the element with high electron affinity, from the viewpoint of being easier to obtain a -1-valent anion and having better machinability, the element of Group 17 is preferred. As the element of Group 17, At, I, Br, Cl and F are preferred.
[0098] The first ionization energy is the energy required to remove an electron from a neutral atom and ionize it. The first ionization energy may be the same as the first ionization energy described in "Shriver·Atkins Inorganic Chemistry (Volume 1) 4th Edition Part I Fundamentals 1. Atomic Structure". The first ionization energy may be converted to the unit of "KJ / mol" from the unit of "eV" of the first ionization energy described in "Shriver·Atkins Inorganic Chemistry (Volume 1) 4th Edition Appendix 2" as 1eV=96.485KJ / mol. The first ionization energy may also be obtained by the photoelectron yield spectroscopy (PYS) method.
[0099] Electron affinity (EA) is the energy released when an electron is introduced into a neutral atom. Electron affinity can be measured by the difference between the ionization potential and the energy gap. The ionization potential is defined as the energy difference between the highest energy occupied orbital in the molecular orbital of a compound and the vacuum energy level, and its value is measured using ultraviolet photoelectron spectroscopy.
[0100] As the first ionization energy and the electron affinity, data stored in the NIST Chemistry WebBook (https: / / webbook.nist.gov / chemistry / ) can also be used (select Ionization Energy or Electron Affinity from Ion energetics properties).
[0101] The first ionization energy and the electron affinity may be measured by appropriately using the above-mentioned methods as long as the ease of forming a +1-valent cation or a -1-valent anion can be compared between other elements to be compared.
[0102] Specific examples of the end-capping element include Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. From the viewpoint of further improving machinability, Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F are preferred.
[0103] In some suitable embodiments, a zirconia composite sintered body can be cited, wherein the element derived from the capping agent includes at least one element selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F, and the ion of the aforementioned element is a +1 valent cation or a -1 valent anion selected from at least one of Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl and F.
[0104] In other suitable embodiments, a zirconia composite sintered body can be cited, wherein the element or ion derived from the capping agent includes at least one element or its ion selected from Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
[0105] The capping element or ion may be used alone or in combination of two or more.
[0106] In the zirconium oxide composite sintered body of the present invention, the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the viewpoint of better light transmittance and strength, it is preferably greater than 79 mol% and less than 96 mol%, more preferably greater than 80 mol% and less than 94 mol%, and further preferably greater than 81 mol% and less than 93 mol%.
[0107] Examples of stabilizers that can inhibit the phase transition of zirconium oxide include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O3), and vanadium oxide (Pr2O3). 11 ), samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3), and ytterbium oxide (Yb2O3), etc., and Y2O3 (yttrium oxide) and / or CeO2 are preferred from the viewpoint of better effects of the present invention, especially excellent aesthetics. The aforementioned stabilizer may be used alone or in combination of two or more.
[0108] As described above, since the capping element or ion functions as a whole with Nb2O5 and / or Ta2O5, the effect of the aforementioned stabilizer is not impaired, and thus the aforementioned stabilizer is not particularly limited and achieves the effect of the present invention.
[0109] In the zirconium oxide composite sintered body of the present invention, the content of the stabilizer capable of inhibiting the phase transformation of zirconium oxide is 1 to 12 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizers, Nb2O5 and Ta2O5. From the perspective of easy acquisition of sufficient machinability, it is preferably from 2 mol% to 10 mol%, and from the perspective of better light transmittance and strength, it is more preferably from 3 mol% to 8 mol%, and further preferably from 3.5 mol% to 7.5 mol%.
[0110] Some suitable embodiments include a zirconia composite sintered body, wherein the stabilizer capable of suppressing the phase transformation of zirconia includes Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is 2 mol% or more and 10 mol% or less.
[0111] As some other suitable embodiments, there can be mentioned a zirconia composite sintered body, in which the stabilizer capable of suppressing the phase transformation of zirconia includes Y 2 O 3 , and the content of Y 2 O 3 is 2 mol % or more and 10 mol % or less.
[0112] In any of the aforementioned embodiments, the contents of Y2O3 and CeO2 may be appropriately changed within the range described in this specification. For example, from the perspective of better light transmittance and strength, the combined content of Y2O3 and CeO2 may be greater than 2.5 mol % and less than 10 mol %, or may be greater than 3 mol % and less than 9 mol %.
[0113] In the zirconia composite sintered body of the present invention, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol% in the total of 100 mol% of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, preferably 1.5 mol% or more and 8.5 mol% or less. From the perspective of functioning in an integrated manner with the end-capping element or ion and having better machinability, it is more preferably 2.5 mol% or more and 8 mol% or less, and further preferably 3 mol% or more and 7 mol% or less. When the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. In addition, when the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, the resulting zirconia composite sintered body will have defects, etc., and it is difficult to obtain sufficient physical properties.
[0114] As described above, Nb2O5 and Ta2O5 act in the direction of coarsening the fine structure and reducing the hardness, and work together with the capping elements or ions to impart excellent machinability. In addition, through the interaction with other components added to the zirconia composite sintered body (such as TiO2, Al2O3) and the application of HIP, the sintering density can be maximized to ensure the aesthetics of natural teeth.
[0115] The content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is a ratio when the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is 100 mol%, and the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 and does not contain Ta2O5, the content of each component of ZrO2, HfO2, stabilizer and Nb2O5 refers to the content ratio relative to the total of ZrO2, HfO2, stabilizer and Nb2O5, which is 100 mol%.
[0116] In addition, when the content of the stabilizer is set to A mol% and the total content of Nb2O5 and Ta2O5 is set to B mol%, from the viewpoint of machinability, the ratio of A / B is preferably 0.9 to 3, more preferably 0.95 to 2, and is further preferably 1 to 1.6 from the perspective of improving the effect of the capping element or ion acting as a whole with Nb2O5 and / or Ta2O5, providing better machinability, suppressing the consumption of processing tools, and further increasing the number of dental prostheses obtained by continuous processing using one processing tool.
[0117] As some suitable embodiments of the present invention, there can be cited a zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5,
[0118] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0119] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0120] The content of the stabilizer is 1 to 12 mol%.
[0121] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0122] The zirconia composite sintered body further comprises a capping element or ion,
[0123] The stabilizer comprises Y2O3 and / or CeO2,
[0124] The content of the aforementioned end-capping element or ion is greater than 0 mol% and less than 5 mol% relative to 100 mol% of the total of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5,
[0125] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0126] As certain embodiments of the present invention, there can be cited a zirconia composite sintered body, which contains, in addition to ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and / or Ta2O5, and a capping element or ion, a zirconia strengthener.
[0127] The zirconia reinforcing agent acts integrally with the capping elements or ions in a zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconia, and Nb2O5 and / or Ta2O5, thereby improving the strength of the sintered body.
[0128] In the zirconia composite sintered body containing zirconia strengthener, the total content of ZrO2 and HfO2, the type and content of stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of capping elements or ions, and the A / B ratio can also be appropriately changed as described above.
[0129] In the zirconia composite sintered body containing a zirconia reinforcing agent, the content of the zirconia reinforcing agent is preferably greater than 0 mass% and less than 5.0 mass% relative to the total of 100 mass% of ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and Ta2O5. From the perspective of functioning as a whole when combined with a capping element or ion and having better strength, it is more preferably greater than 0.01 mass% and less than 4.5 mass%, and further preferably greater than 0.5 mass% and less than 4.0 mass%.
[0130] Examples of the zirconium oxide reinforcing agent include TiO 2 and Al 2 O 3 . The zirconium oxide reinforcing agent may be used alone or in combination of two or more.
[0131] As some suitable embodiments, there can be mentioned a zirconia composite sintered body, in which the zirconia reinforcing agent includes TiO 2 and the content of TiO 2 is 0.6 to 3.7% by mass.
[0132] As some suitable embodiments, there can be mentioned a zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5,
[0133] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0134] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0135] The content of the stabilizer is 1 to 12 mol%.
[0136] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0137] The zirconia composite sintered body further comprises a capping element or ion,
[0138] The stabilizer comprises Y2O3 and / or CeO2,
[0139] The zirconium oxide reinforcing agent contains TiO2, and the content of TiO2 is 0.6 to 3.7% by mass.
[0140] The content of the aforementioned end-capping element or ion is greater than 0 mol% and less than 5 mol% relative to 100 mol% of the total of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5,
[0141] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
[0142] The average grain size of the zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm, and even more preferably 1.0 to 4.0 μm from the viewpoint of better machinability, strength, and light transmittance. The method for measuring the average grain size is described in the Examples below.
[0143] The average grain size can be measured by adjusting the number of particles so that the number of particles included in the SEM photograph image of one field of view is about 50 or 100 in the method described in the Examples.
[0144] The density of the zirconia composite sintered body is preferably 5.5 g / cm2 because the higher the density, the fewer internal voids there are, the less light scattering occurs, the better the light transmittance, and the better the strength. 3 More preferably, 5.7 g / cm 3 More preferably, 5.9 g / cm 3 above.
[0145] It is particularly preferred that the zirconia composite sintered body contains substantially no voids.
[0146] The density of the composite sintered body can be calculated by (mass of the composite sintered body) / (volume of the composite sintered body).
[0147] As another embodiment of the present invention, there is mentioned a method for producing a zirconia composite sintered body, which comprises:
[0148] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,
[0149] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0150] The total content of ZrO2 and HfO2 is 78-97.5 mol%.
[0151] The content of the stabilizer is 1 to 12 mol%.
[0152] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0153] The raw material composition further comprises a capping agent; and
[0154] A step of sintering the molded body.
[0155] The raw material composition of the zirconia composite sintered body includes ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and / or Ta2O5, and a capping agent. The raw material composition of the zirconia composite sintered body may be in a dry state, or in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, powder, granules or granules, paste, slurry, etc.
[0156] The raw material composition includes a capping agent so that the obtained zirconia composite sintered body includes a capping element or ion. As the capping agent, as long as it is a compound that can become a monovalent ion (+1-valent cation or -1-valent anion) in a solvent containing water, there is no particular limitation, for example, hydroxides, salts, halides (fluorides, chlorides, bromides, iodides), cyanides, etc. containing elements or ions derived from the capping agent can be cited. The capping agent can be used alone or in combination of two or more.
[0157] Examples of the hydroxide containing a capping element or ion include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide.
[0158] Examples of the salt containing the capping element or ion include carbonates, hydrogen carbonates, nitrates, hypochlorites, chlorites, chlorates, perchlorates, bromates, permanganates, metaborates, sulfide salts, and cyanide salts.
[0159] Examples of the carbonate containing a capping element or ion include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, and cesium carbonate.
[0160] Examples of the hydrogen carbonate salt containing a capping element or ion include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate.
[0161] Examples of nitrates containing a capping element or ion include calcium nitrate, strontium nitrate, iron (II) nitrate, iron (III) nitrate, cobalt (II) nitrate, magnesium nitrate, gallium nitrate, yttrium (III) nitrate, lanthanum (III) nitrate, praseodymium nitrate, neodymium (III) nitrate, manganese (II) nitrate, europium nitrate, copper (II) nitrate, thorium nitrate, aluminum nitrate, nickel (II) nitrate, chromium (III) nitrate, titanium (IV) nitrate, zirconium nitrate, zirconium (IV) nitrate hydrate (ZrO(NO3)2·xH2O), cerium (III) nitrate, tin nitrate, bismuth (III) nitrate, scandium (III) nitrate, indium (III) nitrate, and hafnium (IV) nitrate.
[0162] Examples of the hypochlorite containing a capping element or ion include sodium hypochlorite and calcium hypochlorite.
[0163] Examples of chlorites containing a capping element or ion include sodium chlorite, potassium chlorite, lithium chlorite, calcium chlorite, magnesium chlorite, barium chlorite, copper (II) chlorite, copper (III) chlorite, silver chlorite, and nickel chlorite.
[0164] Examples of the chlorate containing a capping element or ion include calcium chlorate, barium chlorate, cobalt chlorate, nickel chlorate, magnesium chlorate, zinc chlorate, and copper chlorate.
[0165] Examples of the perchlorate containing a capping element or ion include iron (III) perchlorate, barium perchlorate, calcium perchlorate, cobalt perchlorate, nickel perchlorate, magnesium perchlorate, beryllium perchlorate, aluminum perchlorate, and cerium perchlorate.
[0166] Examples of the bromate containing a capping element or ion include neodymium bromate, lanthanum bromate, and praseodymium bromate.
[0167] Examples of permanganate containing a capping element or ion include calcium permanganate (VII), potassium permanganate (VII), sodium permanganate (VII), and the like.
[0168] Examples of the metaborate containing a capping element or ion include sodium metaborate and barium metaborate.
[0169] Examples of the sulfide salt containing a capping element or ion include copper (I) sulfide and the like.
[0170] Examples of the cyanide salt containing a capping element or ion include barium cyanide, sodium cyanide, potassium cyanide, and calcium cyanide.
[0171] Examples of the fluoride containing a terminal element or ion include lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, francium fluoride, beryllium fluoride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, scandium (III) fluoride, yttrium (III) fluoride, lanthanum (III) fluoride, cerium (III) fluoride, neodymium (III) fluoride, titanium (III) fluoride, titanium (IV) fluoride, zirconium (IV) fluoride, hafnium (IV) fluoride, tantalum (V) fluoride, manganese (II) fluoride, manganese (III) fluoride, iron (II) fluoride, iron (III) fluoride, copper (II) fluoride, zinc (II) fluoride, aluminum fluoride, chromium (III) fluoride, bismuth (III) fluoride, indium (III) fluoride, and tin (II) fluoride.
[0172] Examples of the chloride containing a terminal element or ion include zirconium oxychloride, lithium chloride, sodium chloride, potassium chloride, rubidium chloride, cesium chloride, francium chloride, beryllium chloride, magnesium chloride, calcium chloride, strontium chloride, barium chloride, scandium (III) chloride, yttrium (III) chloride, lanthanum (III) chloride, cerium (III) chloride, praseodymium chloride, neodymium (III) chloride, samarium chloride, europium chloride, titanium (III) chloride, titanium (IV) chloride, zirconium (IV) chloride, hafnium (IV) fluoride, tantalum (V) chloride, manganese chloride, iron (II) chloride, iron (III) chloride, cobalt (II) chloride, nickel (II) chloride, copper (I) chloride, copper (II) chloride, zinc (II) chloride, aluminum chloride, gallium chloride, bismuth (III) chloride, indium (I) chloride, indium (III) chloride, and tin (II) chloride.
[0173] Examples of bromides containing a terminal element or ion include lithium bromide, sodium bromide, potassium bromide, rubidium bromide, cesium bromide, francium bromide, beryllium bromide, magnesium bromide, calcium bromide, strontium bromide, barium bromide, scandium (III) bromide, yttrium (III) bromide, cerium (III) bromide, neodymium (III) bromide, titanium (IV) bromide, zirconium (IV) bromide, tantalum (V) bromide, manganese (II) bromide, iron (II) bromide, iron (III) bromide, cobalt (II) bromide, nickel (II) bromide, copper (I) bromide, copper (II) bromide, zinc (II) bromide, chromium (III) bromide, bismuth (III) bromide, vanadium (III) bromide, indium (III) bromide, and tin bromide.
[0174] Examples of the iodide containing a terminal element or ion include lithium iodide, sodium iodide, potassium iodide, rubidium iodide, cesium iodide, francium iodide, beryllium iodide, calcium iodide, magnesium iodide, strontium iodide, barium iodide, scandium (III) iodide, yttrium (III) iodide, lanthanum (III) iodide, cerium (III) iodide, neodymium (III) iodide, titanium (IV) iodide, zirconium (IV) iodide, hafnium (IV) iodide, tantalum (V) iodide, manganese (II) iodide, iron (II) iodide, iron (III) iodide, cobalt (II) iodide, nickel (II) iodide, copper (I) iodide, zinc (II) iodide, aluminum iodide, chromium (III) iodide, vanadium (II) iodide, bismuth (III) iodide, indium (III) iodide, tin (II) iodide, and tin (IV) iodide.
[0175] As ZrO 2 and HfO 2 , commercially available zirconium oxide powder can be used.
[0176] Commercially available products include, for example, zirconium oxide powder (trade name “Zpex (registered trademark)” (content of Y2O3: 3 mol%), “Zpex (registered trademark) 4” (content of Y2O3: 4 mol%), “Zpex (registered trademark) 4Smile (registered trademark)” (content of Y2O3: 5.5 mol%), “TZ-3Y” (content of Y2O3: 3 mol%), “TZ-3YS” (content of Y2O3: 3 mol%), “TZ-4YS” (content of Y2O3: 4 mol%), “TZ-6Y” (content of Y2O3: 6 mol%), “TZ-6YS” (content of Y2O3: 6 mol%), “TZ-8YS” (content of Y2O3: 8 mol%), and “TZ- Z-10YS" (content of Y2O3: 10 mol%), "TZ-3Y-E" (content of Y2O3: 3 mol%), "TZ-3YS-E" (content of Y2O3: 3 mol%), "TZ-3YB-E" (content of Y2O3: 3 mol%), "TZ-3YSB-E" (content of Y2O3: 3 mol%), "TZ-3YB" (content of Y2O3: 3 mol%), "TZ-3YSB" (content of Y2O3: 3 mol%), "TZ-3Y20AB" (content of Y2O3: 3 mol%), "TZ-8YSB" (content of Y2O3: 8 mol%), "TZ-0" (content of Y2O3: 0 mol%); all of the above are manufactured by Tosoh Corporation), etc. The aforementioned commercially available zirconia powder also contains HfO2. As a commercial product, a product containing Y2O3 may also be used. As the zirconium oxide powder, in the raw material composition of the present invention, a zirconium oxide powder in which Y2O3 is uniformly dispersed and solid-dissolved, such as the aforementioned commercial product TZ series (part of the product name contains "TZ"), may also be used.
[0177] The method for producing the zirconium oxide powder is not particularly limited, and for example, a known method such as a fracturing process in which coarse particles are crushed into fine powder, or a deposition process in which atoms or ions form nuclei and synthesize the particles through a growth process can be used.
[0178] The type of zirconium oxide powder in the raw material composition is not particularly limited. The zirconium oxide powder contains ZrO2 and HfO2. When no stabilizer is contained or when the content of the stabilizer is increased as required, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the zirconium oxide composite sintered body can be adjusted to the above-specified range.
[0179] As the particles of the stabilizer, for example, a commercially available product may be used, or a powder of a commercially available product may be pulverized using a known pulverizing and mixing device (such as a ball mill) and then used.
[0180] The aforementioned stabilizer may be any one of a stabilizer that is insoluble in ZrO 2 and HfO 2 and a stabilizer that is soluble in ZrO 2 and HfO 2 .
[0181] In some suitable embodiments, a method for producing a zirconia composite sintered body can be cited, wherein, in the raw material composition, from the aspect of being a reason for easily obtaining the target zirconia composite sintered body, the stabilizer (suitably Y2O3) includes a stabilizer that is not soluble in ZrO2 and HfO2. For example, it can be confirmed by an X-ray diffraction (XRD; X-Ray Diffraction) pattern that the stabilizer includes a stabilizer that is not soluble in zirconia.
[0182] When a peak derived from a stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, a stabilizer that is not solid-soluble in ZrO 2 and HfO 2 exists in the raw material composition or the molded body.
[0183] When the entire amount of stabilizer is solid-dissolved in ZrO2 and HfO2, the peak derived from the stabilizer cannot be confirmed in the XRD pattern. However, depending on conditions such as the crystal state of the stabilizer, even if there is no peak of the stabilizer in the XRD pattern, the stabilizer may sometimes not be solid-dissolved in ZrO2 and HfO2.
[0184] The case where the stabilizer contains a stabilizer that is not soluble in ZrO 2 and HfO 2 is described below using yttrium oxide as an example.
[0185] In the raw material composition or the molded body of the present invention, the existence ratio of yttrium oxide that is not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttrium oxide") is y It can be calculated based on the following mathematical formula (1).
[0186] f y =I 29 / (I 28 +I 29 +I 30 )×100
[0187] (where f y Indicates the proportion of undissolved yttrium oxide (%). In XRD measurement, I 28 The area intensity of the peak near 2θ = 28° where the main peak of the monoclinic system appears, I 29 The area intensity of the peak near 2θ = 29° where the main peak of yttrium oxide appears, I 30 It indicates the area intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic system appears.
[0188] In addition, when a stabilizer other than yttrium oxide is used simultaneously, by replacing I 29 Substituting the peaks of other stabilizers can also be used to calculate the undissolved existence rate of stabilizers other than yttrium oxide.
[0189] From the viewpoint of easily obtaining the target zirconia composite sintered body, etc., the existence ratio of undissolved yttrium oxide f y It is preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. y The upper limit of γ may be, for example, 25% or less, but it preferably depends on the content of yttrium oxide in the raw material composition or the molded body.
[0190] For example, when the content of yttrium oxide in the raw material composition or the molded body of the present invention is 3 mol% or more and 8 mol% or less, it is as follows.
[0191] When the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f y When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It can be set to 25% or less.
[0192] For example, when the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y It is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and particularly preferably 5% or more.
[0193] When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f yIt is preferably 3% or more, more preferably 4% or more, further preferably 5% or more, further preferably 6% or more, and particularly preferably 7% or more.
[0194] When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, further preferably 7% or more, and particularly preferably 8% or more.
[0195] In the raw material composition or the molded body of the present invention, the stabilizer may not be solid-dissolved in ZrO2 and HfO2 at all. It should be noted that in the present invention, the so-called solid-dissolved stabilizer means, for example, that the elements (atoms) contained in the stabilizer are solid-dissolved in ZrO2 and HfO2.
[0196] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as it can adjust the content of Nb2O5 and / or Ta2O5 contained in the zirconia composite sintered body to the above-mentioned specified range. Nb2O5 and / or Ta2O5 are not particularly limited, for example, commercial products can be used, and powders of commercial products can also be crushed using a known crushing and mixing device (ball mill, etc.) and then used.
[0197] As a process for preparing the raw material composition, for example, there can be cited a method of wet-mixing the raw materials of the aforementioned raw material composition (ZrO2, HfO2, stabilizer, Nb2O5 and / or Ta2O5, a capping agent (for example, a compound that can become a monovalent ion in a solvent containing water), and further a zirconium oxide reinforcing agent as required) in a solvent containing water to obtain the raw material composition.
[0198] The method for wet mixing the aforementioned raw materials in a solvent containing water is not particularly limited. For example, the raw materials can be wet-mixed by a known pulverizing and mixing device (ball mill, etc.) to form a slurry, and then the slurry is dried and granulated to prepare a granular raw material composition.
[0199] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, a defoamer, a pH adjuster, and a lubricant may be further contained. The additives may be used alone or in combination of two or more.
[0200] The aforementioned binder may be prepared by adding a primary powder of a mixture of ZrO2, HfO2, Y2O3, Nb2O5 and / or Ta2O5 and a capping agent to water to prepare a slurry, and then adding the primary powder to the crushed slurry.
[0201] The aforementioned adhesive is not particularly limited, and known adhesives can be used. As the adhesive, for example, polyvinyl alcohol-based adhesives, acrylic adhesives, wax-based adhesives (paraffin, etc.), methylcellulose, carboxymethylcellulose, polyvinyl butyral, polymethyl methacrylate, ethylcellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polystyrene, atactic polypropylene, methacrylic resins, etc. can be cited.
[0202] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.
[0203] Examples of the dispersant include ammonium polycarboxylates (triammonium citrate, etc.), ammonium polyacrylates, acrylic copolymer resins, acrylate copolymers, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate, etc.), nonionic surfactants, olein, amine salt-type surfactants, oligosaccharide alcohols, and stearic acid.
[0204] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.
[0205] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.
[0206] Examples of the pH adjuster include ammonia, ammonium salts (including ammonium hydroxide such as tetramethylammonium hydroxide), and the like.
[0207] Examples of the lubricant include polyoxyethylene alkyl ether and wax.
[0208] The solvent used in wet mixing is not particularly limited as long as it contains water, and an organic solvent, a mixed solvent of water and an organic solvent, or water alone can be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerol, diglycerol, polyglycerol, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.
[0209] The raw material composition of the zirconia composite sintered body used in the present invention may also contain other components besides ZrO2, Y2O3, Nb2O5, Ta2O5, a capping agent, and a zirconia reinforcing agent as required, as long as it achieves the effect of the present invention. Examples of such other components include colorants (pigments and composite pigments), fluorescent agents, SiO2, etc. Other components may be used alone or in combination of two or more.
[0210] Examples of the pigment include oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb, and more preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb. However, Y2O3 and CeO2 may be removed from the pigment.
[0211] Examples of the composite pigment include (Zr, V)O2, Fe(Fe, Cr)2O4, (Ni, Co, Fe)(Fe, Cr)2O4·ZrSiO4, and (Co, Zn)Al2O4.
[0212] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y, Gd, Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O 17 :Eu et al.
[0213] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (such as press molding) can be used.
[0214] When the zirconia molded body is produced by a method including the step of press-molding the raw material composition, the specific method of press-molding is not particularly limited, and a known press-molding machine can be used for the press-molding. Specific methods of press-molding include, for example, uniaxial pressing.
[0215] The pressurization pressure is appropriately set to an optimal value according to the size of the target molded body, the porosity, the biaxial bending strength, and the particle size of the raw material powder, and is generally 5 MPa or more and 1000 MPa or less. By increasing the pressurization pressure during molding in the aforementioned manufacturing method, the pores of the obtained molded body are further filled, the porosity can be set lower, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, cold isostatic pressing (CIP) treatment can be further performed after uniaxial pressing.
[0216] Next, the obtained compact is sintered.
[0217] The term "molded body" refers to a molded body that has not reached any of the semi-sintered state (pre-fired state) and the sintered state. That is, the molded body is formed into a molded body but is not fired, and is distinguished from a pre-fired body and a sintered body in this respect.
[0218] The sintering temperature (maximum sintering temperature) for obtaining the zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, further preferably 1400°C or higher, further preferably 1450°C or higher, and particularly preferably 1500°C or higher. In addition, the sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and further preferably 1600°C or lower. As the method for producing the zirconia composite sintered body of the present invention, it is preferred that the formed body be sintered at a maximum sintering temperature of 1300 to 1680°C. The aforementioned maximum sintering temperature is preferably a temperature in the atmosphere.
[0219] The holding time (retention time) at the maximum sintering temperature also depends on the temperature, but is preferably less than 30 hours, more preferably less than 20 hours, further preferably less than 10 hours, further preferably less than 5 hours, particularly preferably less than 3 hours, and most preferably less than 2 hours. Furthermore, the holding time may also be set to less than 25 minutes, less than 20 minutes or less than 15 minutes. In addition, the holding time is preferably more than 1 minute, more preferably more than 5 minutes, and more preferably more than 10 minutes. According to the manufacturing method of the present invention, according to the content of the stabilizer, a zirconia composite sintered body with excellent bending strength, light transmittance and machinability can be produced. In addition, as long as the effect of the present invention can be obtained, the sintering time can also be shortened. By shortening the sintering time, production efficiency can be improved while reducing energy costs.
[0220] In the method for producing a zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.
[0221] In the process of sintering the molded body, a general dental zirconia sintering furnace can be used. As a dental zirconia sintering furnace, a commercial product can also be used. As commercial products, Noritake Katana (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be cited.
[0222] Furthermore, the step of sintering the formed body preferably includes a step of performing a hot isostatic pressing (HIP) treatment in addition to the sintering at the highest sintering temperature. The HIP treatment can further improve the light transmittance and strength of the zirconia composite sintered body.
[0223] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after HIP treatment is referred to as a "HIP treatment sintered body".
[0224] The HIP treatment can be performed using a known hot isostatic pressing (HIP) apparatus.
[0225] The temperature of the HIP treatment is not particularly limited, but from the perspective of obtaining a high-strength, dense zirconia composite sintered body, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and further preferably 1400° C. or higher. In addition, the HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and further preferably 1600° C. or lower.
[0226] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited. From the perspective of obtaining a dense sintered body with high strength, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and further preferably 130 MPa or more. In addition, the upper limit of the HIP pressure is not particularly limited, and can be, for example, 400 MPa or less, 300 MPa or less, and further 200 MPa or less.
[0227] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.
[0228] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP time is not particularly limited. From the perspective of obtaining a high-strength and dense zirconia composite sintered body, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. In addition, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.
[0229] In the method for manufacturing a zirconium oxide composite sintered body of the present invention, when the aforementioned primary sintered body is subjected to HIP treatment, the pressure medium is not particularly limited. From the viewpoint of having a low impact on zirconium oxide, the pressure medium can be selected from at least one of oxygen, oxygen containing 3% hydrogen, air and an inert gas (such as nitrogen, argon, etc.).
[0230] When the primary sintered body is subjected to the HIP treatment in an oxygen mixed gas atmosphere, the oxygen concentration is not particularly limited, and can be, for example, greater than 0% and 20% or less.
[0231] When the oxygen mixed gas is used, as a gas other than oxygen, at least one inert gas (for example, nitrogen, argon, etc.) can be selected.
[0232] In the method for manufacturing a zirconia composite sintered body of the present invention, if the aforementioned HIP treatment is performed in a reducing atmosphere using an inert gas or the like, blackening may sometimes occur due to oxygen defects. In this case, in order to remove the blackening, it is preferably included in the step of performing a heat treatment in the atmosphere or in an oxygen-excess atmosphere at a temperature below 1650°C after the aforementioned HIP treatment step (hereinafter also referred to as "tempering treatment"), and from the viewpoint of effectively performing the heat treatment, it is more preferably performed in an oxygen-excess atmosphere. "Oxygen-excess atmosphere" means an oxygen concentration greater than that in the atmosphere. As an oxygen-excess atmosphere, there is no particular limitation as long as the oxygen concentration is greater than 21% and less than 100%, and it can be appropriately selected from this range. For example, the oxygen concentration can also be set to 100%.
[0233] The zirconia composite sintered body of the present invention is not particularly limited as long as it can achieve the effects of the present invention, and may be a primary sintered body, a HIP-treated sintered body, or a tempered sintered body.
[0234] As some suitable embodiments, there can be mentioned a zirconia composite sintered body which is a sintered body after tempering treatment.
[0235] The temperature of the heat treatment in the air or in an oxygen-excess atmosphere may be appropriately changed according to the aesthetic properties of the zirconia composite sintered body (for example, the color of a dental prosthesis).
[0236] In certain suitable embodiments, from the viewpoint of the aesthetics of the zirconia composite sintered body, the temperature of the heat treatment in air or in an oxygen-excess atmosphere is preferably 1650° C. or lower, more preferably 1600° C. or lower, and further preferably 1550° C. or lower.
[0237] In other suitable embodiments, from the viewpoint of the aesthetics of the zirconia composite sintered body, the temperature of the heat treatment in air or in an oxygen-excess atmosphere is preferably 1400° C. or lower, more preferably 1300° C. or lower, and further preferably 1200° C. or lower.
[0238] Furthermore, in any embodiment, the temperature of the heat treatment is preferably 500° C. or higher, more preferably 600° C. or higher, and even more preferably 700° C. or higher.
[0239] In the above-mentioned tempering treatment, a general dental zirconia firing furnace can be used. As a dental zirconia firing furnace, a commercial product can also be used. As commercial products, Noritake Katana (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be cited.
[0240] The zirconia composite sintered body of the present invention is a sintered body, but has excellent machinability, so it is not necessary to machine a semi-sintered pre-calcined body in a ground state and then sinter it to obtain a sintered body.
[0241] On the other hand, the method for producing the zirconium oxide composite sintered body may be a method of pre-sintering a molded body obtained using the raw material composition to produce a semi-sintered pre-sintered body, and machining the unprocessed pre-sintered body to produce a sintered body.
[0242] As some other embodiments, there is provided a method for producing a zirconia composite sintered body, which includes: a step of preparing a formed body using the raw material composition, a step of pre-firing the obtained formed body to obtain a zirconia calcined body (pre-firing step), and a step of sintering the zirconia calcined body.
[0243] In order to reliably perform agglomeration, the firing temperature (pre-firing temperature) in the pre-firing step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and further preferably 950° C. or higher.
[0244] The calcining temperature is preferably, for example, 1200° C. or less, more preferably 1150° C. or less, and further preferably 1100° C. or less. The calcining temperature is preferably, for example, 800° C. to 1200° C. It is considered that at such a calcining temperature, the stabilizer will not be dissolved to a large extent in the calcining step.
[0245] The calcined zirconium oxide of the present invention refers to a state in which ZrO2 particles are necked (fixed) to each other and the ZrO2 particles (powder) are not completely sintered (semi-sintered state).
[0246] The density of the calcined zirconium oxide is preferably 2.7 g / cm 3 In addition, the density of the zirconia calcined body is preferably 4.0 g / cm 3 Below, more preferably 3.8 g / cm 3 Below, more preferably 3.6 g / cm 3When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, in the form of (mass of the calcined body) / (volume of the calcined body).
[0247] The three-point bending strength of the calcined zirconium oxide body is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, and even more preferably 20 to 50 MPa.
[0248] The bending strength can be measured as follows: using a test piece of thickness 5mm×width 10mm×length 50mm, except for the size of the test piece, the test is performed in accordance with ISO 6872:2015. The surface of the test piece and the C surface (the surface obtained by chamfering the corner of the test piece at an angle of 45°) are surface-finished along the length direction using 600 sandpaper. The test piece is configured in a manner that the widest surface faces the vertical direction (load direction). In the bending test measurement, the span is set to 30mm and the crosshead speed is set to 1.0mm / minute.
[0249] The step of sintering the zirconia calcined body can be performed by the same method and conditions (temperature, pressure, etc.) as the step of sintering the molded body. Therefore, in the embodiment of the manufacturing method using the zirconia calcined body, the "molded body" may be replaced with the "calcined body".
[0250] The zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the zirconia composite sintered body of the present invention is preferably 300 MPa or more, more preferably 350 MPa or more, further preferably 400 MPa or more, further preferably 450 MPa or more, and particularly preferably 500 MPa or more. By making the zirconia composite sintered body of the present invention have such biaxial bending strength, for example, when used as a dental prosthesis, it is possible to suppress breakage in the oral cavity. There is no particular restriction on the upper limit of the biaxial bending strength, but the biaxial bending strength can be set to, for example, 1200 MPa or less, and further 1000 MPa or less. It should be noted that the biaxial bending strength of the zirconia composite sintered body can be measured according to ISO 6872:2015.
[0251] The zirconia composite sintered body of the present invention preferably has high light transmittance. Light transmittance can be evaluated by ΔL*. Regarding light transmittance, specifically, the zirconia composite sintered body of the present invention preferably has a ΔL* of 10 or more when the diameter is 15 mm and the thickness is 1.2 mm, more preferably 12 or more, further preferably 13 or more, and particularly preferably 14 or more. By making the ΔL* within the above range, a zirconia composite sintered body with high light transmittance can be obtained.
[0252] ΔL* refers to the difference between the brightness of the same sample under a white background (first L* value) and the brightness under a black background (second L* value). Specifically, it refers to the difference between the L* value under a white background (JIS Z 8781-4:2013 Color Measurement-Part 4: CIE1976 L*a*b* Color Space) and the L* value under a black background. The white background refers to the white part of the obscuration test paper described in JIS K 5600-4-1:1999 Part 4 Section 1, and the black background refers to the black part of the aforementioned obscuration test paper.
[0253] The upper limit of ΔL* is not particularly limited, and may be, for example, 25 or less, and may further be 20 or less from the viewpoint of aesthetics.
[0254] It should be noted that ΔL* when the zirconia composite sintered body has a diameter of 15 mm and a thickness of 1.2 mm can be measured using a spectrophotometer, for example, a dental colorimetric device ("Crystaleye CE100-CE / JP", 7-band LED light source, and analysis software "Crystaleye" (manufactured by Olympus Corporation)).
[0255] As some other embodiments, there can be mentioned a zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5.
[0256] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0257] The total content of ZrO2 and HfO2 is 73 to 97.5 mol%.
[0258] The content of the stabilizer is 1 to 25 mol%.
[0259] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0260] The zirconia composite sintered body further comprises elements or ions derived from a capping agent,
[0261] The b* value under a white background of the L*a*b* colorimetric system measured using a sample having a thickness of 1.2 mm is 5 or more (hereinafter also referred to as "zirconia composite sintered body having a b* value of 5 or more").
[0262] In dental treatment, different color types such as a dental prosthesis with a strong white color or a dental prosthesis closer to the color of natural teeth are sometimes required according to the patient's wishes. In this case, a dental prosthesis having a color type corresponding to the patient's wishes is manufactured based on a dental color guide. Natural teeth have a yellow tint, but a sintered body of ZrO2 has almost no yellow tint, so a yellow tint is given by adding a pigment or CeO2. On the other hand, depending on the amount of pigment or CeO2 added, light transmittance and / or strength may be reduced.
[0263] In the aforementioned zirconia composite sintered body with a b* value of 5 or more, in addition to having strength and light transmittance suitable for dental use and excellent machinability, it also has a yellow hue close to the colorimetric guide even without adding a pigment or stabilizer CeO2 for imparting a yellow hue. Therefore, there is no need to add pigments or CeO2. By adding pigments or CeO2, a reduction in light transmittance and / or strength can be prevented.
[0264] In the zirconia composite sintered body having a b* value of 5 or more, the type of the stabilizer and the type of the element or ion derived from the capping agent may be the same as in the above embodiment.
[0265] As some suitable embodiments, from the perspective of achieving better effects of the present invention, especially better aesthetics, there can be cited a zirconia composite sintered body in which the b* value is greater than 5 and the stabilizer is Y2O3 (yttrium oxide) and / or CeO2.
[0266] In the aforementioned zirconium oxide composite sintered body having a b* value of 5 or more, the total content of ZrO2 and HfO2 is 73 to 97.5 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the perspective of better light transmittance and strength, it is preferably 74 mol% or more and 96 mol% or less, more preferably 75 mol% or more and 94 mol% or less, and further preferably 75.5 mol% or more and 93 mol% or less.
[0267] In the aforementioned zirconia composite sintered body having a b* value of 5 or more, the content of the stabilizer capable of inhibiting the phase transformation of zirconia is 1 to 25 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5, preferably greater than 2 mol% and less than 20 mol%, and in terms of better light transmittance and strength, more preferably greater than 3 mol% and less than 10 mol%, and further preferably greater than 3.5 mol% and less than 8 mol%.
[0268] The content of the stabilizer in the zirconia composite sintered body having a b* value of 5 or more may be greater than 12 mol%, unlike the above-mentioned embodiment. For example, in the zirconia composite sintered body having a b* value of 5 or more, Y2O3 may be 3.5 mol% or more and 8 mol% or less, and the stabilizer other than Y2O3 may be 1 mol% or more and 10 mol% or less.
[0269] In the aforementioned zirconia composite sintered body having a b* value of 5 or more, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5, preferably 1.5 mol% or more and 8.5 mol% or less, and from the viewpoint of acting on the end-capping element or ion as a whole and having better machinability, it is more preferably 2.5 mol% or more and 8 mol% or less, and further preferably 3 mol% or more and 7 mol% or less. When the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. In addition, when the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, the obtained zirconia composite sintered body will have defects, etc., and it is difficult to obtain sufficient physical properties.
[0270] The b* value is preferably 5.5 or more, more preferably 6.0 or more, further preferably 8.0 or more, and particularly preferably 9.0 or more, from the viewpoint of being closer to the yellow tone of natural teeth.
[0271] The method for measuring the b* value is described in the examples described later.
[0272] In the manufacture of the aforementioned zirconium oxide composite sintered body having a b* value of 5 or more, a raw material composition is used which comprises ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconium oxide (suitably Y2O3), and Nb2O5 and / or Ta2O5, and at least a portion of the stabilizer is solid-dissolved in ZrO2 and HfO2.
[0273] If a raw material composition in which at least a portion of such a stabilizer is solid-dissolved is used, the stabilizer ions (e.g., Y 3+ ) After segregation at the grain boundaries, it exists locally unevenly to form thermally stable cubic crystals.
[0274] In the present invention, it is speculated that by using Nb2O5 and / or Ta2O5, elements or ions derived from the capping agent (such as Na + ) in the presence of at least a portion of the stabilizer solid solution of the raw material composition, the stabilizer ions (such as Y 3+ ) and Nb2O5 and / or Ta2O5, elements or ions derived from the capping agent (e.g. Na + ) reacts and turns yellow.
[0275] In the aforementioned zirconia composite sintered body having a b* value of 5 or more, the elements or ions derived from the capping agent are preferably Cu, Ag, Li, Na, K, Rb, Cs, F and their ions, and more preferably Li, Na, K and their ions.
[0276] In the aforementioned zirconia composite sintered body having a b* value of 5 or more, it is preferably greater than 0 mol% and less than 5 mol%, and from the viewpoint of excellent machinability and being able to further increase the number of dental prostheses that can be continuously processed with one processing tool, it is more preferably from 0.05 mol% to 3 mol%, further preferably from 0.06 mol% to 2.5 mol%, particularly preferably from 0.07 mol% to 1.0 mol%, and most preferably from 0.08 mol% to 0.34 mol%.
[0277] In addition, when the capping element or ion contained in the aforementioned zirconia composite sintered body having a b* value of 5 or more is a Group 17 element or ion, it is more preferably 0.2 mol% to 5 mol%, further preferably 0.3 mol% to 4 mol%, particularly preferably 0.4 mol% to 3.5 mol%, and most preferably 0.5 mol% to 3.0 mol%, from the viewpoint of better machinability and further increasing the number of dental prostheses that can be continuously processed with one processing tool.
[0278] The zirconia composite sintered body having a b* value of 5 or more may further contain a zirconia reinforcing agent. The type and content of the zirconia reinforcing agent may be the same as those in the above embodiment.
[0279] As some suitable embodiments, from the perspective of having a better effect of the present invention, especially functioning as a whole when combined with a capping element or ion, and having better strength, a zirconia composite sintered body in which the b* value is greater than 5 and the zirconia reinforcer is TiO2 can be cited.
[0280] In the above-mentioned preferred embodiment, there can be mentioned a zirconia composite sintered body in which the above-mentioned b* value is 5 or more, the zirconia reinforcing agent is TiO 2 , and the content of TiO 2 is 0.6 to 3.7% by mass.
[0281] The average grain size of the zirconia composite sintered body having a b* value of 5 or more may be the same as that of the above-mentioned embodiment.
[0282] As a method for producing the zirconia composite sintered body having a b* value of 5 or more, for example, there can be mentioned a method for producing the zirconia composite sintered body, which comprises:
[0283] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,
[0284] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,
[0285] The total content of ZrO2 and HfO2 is 73 to 97.5 mol%.
[0286] The content of the stabilizer is 1 to 25 mol%.
[0287] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.
[0288] The raw material composition further comprises a capping agent, at least a portion of the aforementioned stabilizer is solid-dissolved in ZrO2 and HfO2; and
[0289] A step of sintering the molded body.
[0290] The method for producing the zirconia composite sintered body is the same as the above-mentioned method except that at least a part of a stabilizer for solid solution of ZrO 2 and HfO 2 is used in the raw material composition.
[0291] Among the aforementioned stabilizers, those in which 50% or more of the amount of the stabilizer contained in the raw material composition is solid-dissolved in ZrO 2 and HfO 2 may be used.
[0292] As a raw material containing ZrO 2 , HfO 2 , and at least a part of a stabilizer which is solid-dissolved in ZrO 2 and HfO 2 , a commercially available zirconium oxide powder can be used.
[0293] As the commercially available zirconium oxide powder, a zirconium oxide powder in which Y 2 O 3 is uniformly dispersed and solid-solved, such as the aforementioned commercially available TZ series (a part of the product name contains "TZ"), can be used.
[0294] As dental prostheses manufactured using the zirconia composite sintered body of the present invention, for example, in addition to crown restorations such as inlays, onlays, veneers, crowns, core crowns, bridges, etc., abutments, dental posts, dentures, denture bases, implant components (fixtures, bases), etc. can also be cited. In addition, machining is preferably performed using, for example, a commercially available dental CAD / CAM system. As examples of the CAD / CAM system, the CEREC system manufactured by Dentsply Sirona Dental Systems Co., Ltd. and the "KATANA (registered trademark) system" manufactured by Kuraray Noritake Dental Co., Ltd. can be cited.
[0295] Furthermore, the zirconia composite sintered body of the present invention can be used for applications other than dental applications, and is particularly suitable for zirconia components that require a different or complex shape and strength.
[0296] Compared with sintered bodies manufactured only by existing manufacturing methods (injection molding, CIP, casting molding or 3D printing, etc.), the zirconia composite sintered body of the present invention can directly process the sintered body. Therefore, it is economical to obtain the desired zirconia component in a short time, for example. In the case of complex-shaped parts that are difficult to manufacture by previous manufacturing methods, it is not necessary to obtain multiple components by mechanical interlocking, so that a zirconia component with high strength can be obtained. Furthermore, since the sintered body can be directly processed, when dimensional accuracy is required, there is no need for a sintering process, and there is no uneven firing shrinkage, so that the zirconia component can be obtained with high precision. Specifically, it can also be used as a method for manufacturing jewelry decoration purposes, engine components and internal components for aircraft, automobiles, etc., frame materials for display panels, building components, electrical product components, household goods components, and toy components.
[0297] Furthermore, the present zirconia component may be used as a composite component by fitting it with a different type of material.
[0298] The present invention includes various embodiments in which all or part of the above-described configurations are combined within the scope of the technical concept of the present invention as long as the effects of the present invention are achieved.
[0299] Example
[0300] Hereinafter, the present invention will be further specifically described by giving examples, but the present invention is not limited to these examples, and a person with common knowledge in the art can make various modifications within the scope of the technical concept of the present invention. It should be noted that in the following examples and comparative examples, the average particle size is the average primary particle size, which can be obtained by a laser diffraction scattering method. Specifically, a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) can be used to measure a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium on a volume basis.
[0301] [Examples 1 to 43 and Comparative Examples 1 to 10]
[0302] The measurement samples of the examples and comparative examples were produced through the steps of producing a granular raw material composition, producing a compact, and producing a sintered body (producing a primary sintered body, HIP treatment, and tempering treatment).
[0303] [Preparation of Granular Raw Material Composition]
[0304] In order to prepare the granular raw material composition of each embodiment and comparative example, commercially available ZrO2 powder, Y2O3 powder, Nb2O5 powder, Ta2O5 powder, a capping agent, and further TiO2 powder or Al2O3 powder as required are mixed to form the composition described in Tables 1 to 3, water is added to prepare a slurry, and wet pulverization and mixing are carried out with a ball mill until the average particle size becomes less than 0.13μm. After adding a binder to the pulverized slurry, it is dried with a spray dryer to prepare a granular raw material composition (hereinafter also referred to as "raw material composition") for the manufacture of the molded body described later. The above average particle size is a value measured by a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and measured on a volume basis.
[0305] It should be noted that in Example 5, TZ-3Y (Y2O3 content: 3 mol%):TZ-6Y (Y2O3 content: 6 mol%) = 18.7:81.3 were mixed, and the ratio of each component was adjusted to become the blending ratio described in Table 1.
[0306] The ratio in Example 30 was adjusted so that the ratio of each component became the blending ratio described in Table 2, and the mixture was mixed at ZrO 2 :Y 2 O 3 :TZ-6Y=44.76:5.23:50:00.
[0307] [Production of Molded Body]
[0308] For each of the Examples and Comparative Examples, a pellet-shaped molded body and a block-shaped molded body were produced as follows to obtain sintered body samples for evaluation of light transmittance and strength and for evaluation of processability.
[0309] For the pellet-shaped compact, a cylindrical mold having a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the zirconium oxide composite sintered body after sintering was 1.2 mm.
[0310] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a pellet-shaped compact.
[0311] In addition, for the block-shaped compact, the raw material composition was placed in a mold having an inner dimension of 19 mm×18 mm so that the height of the zirconia composite sintered body after sintering was 14.5 mm.
[0312] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a block-shaped compact.
[0313] [Production of primary sintered body]
[0314] The obtained particle-shaped and block-shaped formed bodies were kept in the atmosphere at the highest sintering temperature listed in Tables 1 to 3 for 2 hours using the sintering furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., to obtain particle-shaped and block-shaped zirconium oxide composite sintered body (primary sintered body) samples.
[0315] [Production of HIP-treated sintered body]
[0316] For the obtained particle-shaped and block-shaped zirconium oxide composite sintered bodies (primary sintered bodies), the HIP device "O2-Dr.HIP" manufactured by Kobe Steel, Ltd. was used to retain the bodies at the HIP temperature listed in Tables 1 to 3 at 150 MPa for 2 hours, thereby obtaining samples of particle-shaped and block-shaped zirconium oxide composite sintered bodies (HIP treated sintered bodies).
[0317] [Production of zirconia composite sintered body (sintered body after tempering)]
[0318] The obtained zirconia composite sintered bodies in particle shape and block shape (HIP treated sintered bodies) were retained at 700°C for 60 hours using a sintering furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., thereby obtaining samples of zirconia composite sintered bodies in particle shape and block shape (sintered bodies after tempering treatment). The size of the obtained samples was 15 mm in diameter × 1.2 mm in thickness for the particle shape and 15.7 mm in width × 16.5 mm in length × 14.5 mm in height for the block shape.
[0319] In addition, the content rate of each component of the sintered compact in Table 1 - Table 3 is the value calculated from the charge amount of a raw material.
[0320] The contents (mol %) of the terminal elements or ions in Tables 1 to 3 are external addition rates relative to 100 mol % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizer (yttrium oxide), Nb 2 O 5 and Ta 2 O 5 .
[0321] The contents (mol%) of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5 in Tables 1 to 3 are the contents of each component in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5. Only for ZrO2 and HfO2, it is expressed as the total content of ZrO2 and HfO2.
[0322] The contents (mass %) of TiO 2 and Al 2 O 3 in Tables 1 to 3 are external addition rates relative to 100 mass % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizers, Nb 2 O 5 and Ta 2 O 5 .
[0323] A / B in Tables 1 to 3 represents the ratio of A to B when the content of Y2O3 is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %.
[0324] [Evaluation of light transmittance of zirconia composite sintered body]
[0325] The sample (diameter about 15 mm×thickness 1.2 mm) of the particle-shaped zirconia composite sintered body (sintered body after tempering treatment) of each example and comparative example was used as it is, and the light transmittance was evaluated by the following method (n=3). As a measuring device, a dental colorimetric device "Crystaleye" (7-band LED light source) manufactured by Olympus Corporation was used. First, the background (underlay) of the sample was set to white (the side opposite to the measuring device with respect to the sample was set to white), and the L* value of the L*a*b* colorimetric system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE1976 L*a*b* color space) was measured as the first L* value. Next, for the same sample for which the first L* value was measured, the background (underlay) of the sample was set to black (the side opposite to the measuring device with respect to the sample was set to black), and the L* value of the L*a*b* colorimetric system was measured as the second L* value.
[0326] In the present invention, the difference between the first L* value and the second L* value (the value after deducting the second L* value from the first L* value) is set as the light transmittance, expressed as ΔL*. If ΔL* is high, it means that the light transmittance is high, and if ΔL* is low, it means that the light transmittance is low. In the colorimetric measurement, the black and white used as the background (underlay) used the obscuration test paper used in the measurement of coatings described in JIS K 5600-4-1:1999. The average value of ΔL* of each sample is shown as the result in Tables 1 to 3.
[0327] A value of 10 or more was considered acceptable as ΔL*.
[0328] [Evaluation of color tone of zirconia composite sintered body]
[0329] The samples (diameter about 15 mm×thickness 1.2 mm) of the particle-shaped zirconium oxide composite sintered bodies (sintered bodies after tempering) of the examples and comparative examples were used as they were, and the color tone was evaluated by the following method (n=3). As a measuring device, a dental colorimetric device "Crystaleye" (7-band LED light source) manufactured by Olympus Corporation was used, and the background (underlay) of the sample was set to white (the side opposite to the measuring device was set to white with respect to the sample), and L* and b* of the L*a*b* colorimetric system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) were measured. In the measurement, the white background (underlay) was used as the obscuration test paper used for the measurement of coatings described in JIS K 5600-4-1:1999.
[0330] In Example 29, L* was 87.9 and b* was 8.2.
[0331] In Example 30, L* was 84.3 and b* was 5.3.
[0332] In Example 31, L* was 80.6 and b* was 10.4.
[0333] In Example 32, L* was 89.4 and b* was 3.5.
[0334] [Strength Evaluation of Zirconia Composite Sintered Body]
[0335] The samples of the particle-shaped zirconia composite sintered bodies (tempered sintered bodies) of the examples and comparative examples were used as they were, and the biaxial bending strength (n=5) was measured in accordance with ISO6872:2015 using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) with the crosshead speed set to 1.0 mm / min. The average values are shown in Tables 1 to 3 as the measurement results. As for the strength, 300 MPa or more was considered acceptable.
[0336] [Method for measuring average grain size in sintered body]
[0337] In the particle-shaped zirconium oxide composite sintered body (tempered sintered body) of each example and comparative example, a surface image was obtained using a scanning electron microscope (trade name "VE-9800", manufactured by Keyence Co., Ltd.). After recording the grain boundaries of each crystal particle on the obtained image, the average grain size was calculated by image analysis.
[0338] In the measurement of the average grain size, the image analysis software (trade name "Image-Pro Plus", manufactured by Bodong Co., Ltd.) is used to binarize the read SEM image, adjust the brightness range in a manner that the grain boundary becomes clear, and identify the particles from the field of view (area). The grain size obtained by using Image-Pro Plus refers to: for the length of the line segment obtained by connecting the contour lines passing through the center of gravity obtained by the contour lines of the crystal particles, the grain size obtained by measuring and averaging with the center of gravity and a scale of 2 degrees, in the SEM photo images (3 fields of view) of each embodiment and comparative example, the average value of the grain size of all particles not involving the end of the image is set as the average grain size (number basis) in the sintered body.
[0339] "Particles not involving the image ends" refers to particles within the SEM photo image except for particles whose outlines do not completely fall within the screen (particles whose outlines are disconnected at the upper, lower, left, and right boundaries). The grain size of all particles not involving the image ends is selected in Image-Pro Plus using the option to exclude particles on all boundaries.
[0340] The average grain size of the crystal particles in the zirconia composite sintered body of Example 1 was 2.7 μm, and the average grain size of the crystal particles in the zirconia composite sintered body of Example 13 was 2.2 μm.
[0341] [Evaluation of processability of zirconia composite sintered body]
[0342] For the block-shaped zirconia composite sintered body (tempered sintered body) samples of each embodiment and comparative example, 30 samples with metal fixtures bonded to the surface of about 15.7 mm in width and 14.5 mm in height were prepared and processed into the crown shape of general front teeth using the CEREC system "MC-XL" (manufactured by Dentsply Sirona). The processing program used the software "inLab (registered trademark) CAMvirsion20.0.1.203841", selected Manufacturer: IVOCLAR VIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16, and the processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.
[0343] [Processing time]
[0344] The processing times shown in Tables 1 to 3 are the times required to complete processing of the first sample from the start of processing of the sample under the conditions described in the above [Evaluation of Processability of Zirconia Composite Sintered Body] using a new processing tool.
[0345] In addition, if an error occurs due to the load during processing and the CEREC system "MC-XL" stops processing, a new processing tool is replaced and processing is restarted. This operation is repeated until one sample is processed, and the required time is taken as the processing time.
[0346] [Number of pieces processed]
[0347] The number of samples processed shown in Tables 1 to 3 refers to the number of samples that can be processed into the crown shape of the front teeth without changing the processing tools once, using a new set of processing tools and starting the processing of the samples under the conditions described in the above [Evaluation of the processability of the zirconia composite sintered body]. The maximum number of samples used in the test was 30, and when 30 samples were processed with one processing tool, no additional processing test was performed, and it was always set as "30 or more".
[0348] In addition, before the processing of the first sample is completed, an error occurs due to the load during processing, etc., and the MC-XL stops processing in the middle, and then replaces it with a new processing tool and restarts the processing. Repeat this operation until one sample is processed, and the reciprocal of the number of processing tools used is taken as the number of processing. For example, "0.2" in Comparative Example 1 of Table 3 means that 5 processing tools are used to obtain a sample processed into the shape of a crown of a front tooth. The results are shown in the following Tables 1 to 3.
[0349]
Table 1
[0350]
[0351]
Table 2
[0352]
[0353]
Table 3
[0354]
[0355] The above results confirm that the zirconia composite sintered body of the present invention has strength and light transmittance suitable for dental use and excellent machinability. In addition, in Examples 1 to 43, the consumption of processing tools can be suppressed, and the number of dental prostheses that can be continuously processed by one processing tool can be increased compared to the prior art.
[0356] In Examples 29 to 31, the strength and light transmittance suitable for dental use were achieved, and excellent machinability was achieved, and a yellow hue was imparted.
[0357] On the other hand, in Comparative Examples 1 and 10 containing no terminal element or ion, the reduction in processing time was insufficient.
[0358] In Comparative Examples 2 and 4 containing a divalent metal element which is a metal element not included in the terminal element, the reduction in processing time was insufficient.
[0359] In Comparative Examples 3 and 5 containing a trivalent metal element which is not included in the terminal element, the reduction in processing time was insufficient.
[0360] In Comparative Example 7 in which the content of Nb2O5 was too low, the shortening of the processing time was insufficient.
[0361] In Comparative Example 8 in which the Y2O3 content was too high, the reduction in processing time was insufficient.
[0362] In Comparative Example 6 in which the content of Nb2O5 was too high and Comparative Example 9 in which the content of Y2O3 was too low, defects or peeling occurred in the samples, and physical properties could not be measured.
[0363] In addition, in Patent Document 1, if the addition amount of TiO2 is increased, the strength decreases in proportion to the addition amount (Figure 7), but in the zirconia composite sintered body of the present invention, based on the comparison between Examples 3 and 11, it was confirmed that when containing Nb2O5 and / or Ta2O5 as components, by also including capping elements or ions, TiO2 acts as a whole and can improve the strength of the zirconia composite sintered body.
[0364] Industrial Applicability
[0365] The zirconia composite sintered body of the present invention has appropriate strength and light transmittance and is excellent in machinability, and is particularly useful as a dental material such as a dental prosthesis for dental treatment purposes.
[0366] Explanation of symbols
[0367] 1 Zirconia particles
[0368] 2 peeling ingredients
[0369] 3. Adhesive ingredients
[0370] 4. There is no grain boundary of peeling component
Claims
1. A zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of inhibiting phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The zirconia composite sintered body further includes elements or ions derived from a capping agent.
2. The zirconia composite sintered body according to claim 1, wherein The content of the element or ion derived from the capping agent is greater than 0 mol % and less than 5.0 mol % relative to 100 mol % of the total of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 and Ta 2 O 5 .
3. The zirconia composite sintered body according to claim 1 or 2, wherein: The element or ion derived from the capping agent is an element or ion belonging to the 2nd to 7th periods of the periodic table and having a first ionization energy smaller than that of the Group 18 elements in the same period and / or an element or ion having a high electron affinity.
4. The zirconia composite sintered body according to claim 3, wherein: The aforementioned element or ion derived from the capping agent includes at least one element or ion thereof selected from Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl and F.
5. The zirconia composite sintered body according to any one of claims 1 to 4, wherein When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.
6. The zirconia composite sintered body according to any one of claims 1 to 5, wherein The aforementioned stabilizer includes Y2O3 and / or CeO2.
7. The zirconia composite sintered body according to any one of claims 1 to 6, wherein It also contains a zirconium oxide reinforcing agent, and the content of the above-mentioned zirconium oxide reinforcing agent is greater than 0 mass% and is 5.0 mass% or less relative to 100 mass% of the total of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5.
8. The zirconia composite sintered body according to claim 7, wherein: The aforementioned zirconium oxide reinforcing agent includes TiO2 and / or Al2O3.
9. The zirconia composite sintered body according to claim 7, wherein: The zirconium oxide reinforcing agent contains TiO 2 , and the content of TiO 2 is 0.6 to 3.7% by mass.
10. The zirconia composite sintered body according to any one of claims 1 to 9, wherein The average grain size of the aforementioned zirconium oxide composite sintered body is 0.5 to 5.0 μm.
11. The method for producing a zirconia composite sintered body according to claim 1, comprising: A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The raw material composition further comprises a capping agent; and A step of sintering the molded body.
12. The method for producing a zirconia composite sintered body according to claim 11, wherein: The terminal blocking agent contained in the raw material composition is a compound capable of forming a monovalent ion. The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.
13. The method for producing a zirconia composite sintered body according to claim 11 or 12, wherein: In the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO 2 and HfO 2 .
14. The method for producing a zirconia composite sintered body according to any one of claims 11 to 13, wherein: The step of sintering the molded body comprises: The sintering process is performed at 1300-1680°C, and A process of performing HIP treatment at 1200°C or above.
15. The method for producing a zirconia composite sintered body according to claim 14, wherein: The method includes the step of performing a heat treatment at 1400° C. or lower in the air or in an atmosphere containing excess oxygen after performing the HIP treatment.
Citation Information
Patent Citations
Machinable zirconia and method for producing the same
JP2015127294A
Production method for workable zirconia composite sintered body, raw material composition for workable zirconia composite sintered body, and workable zirconia composite calcined body
WO2021132644A1
Calcined zirconia object suitable for dentistry
CN113194905A
METHOD FOR MANUFACTURED A RED-COLOURED ARTICLE, RED-COLOURED ARTICLE, ITS USES AND A PART INCLUDING SUCH AN ARTICLE
FR3088637A1
High thermal expansion coefficient ceramic sinter and a composite body of the same and metal
US5043305A